2022
DOI: 10.1097/scs.0000000000009094
|View full text |Cite
|
Sign up to set email alerts
|

Patient Safety and Quality Improvement Initiatives in Cleft Lip and Palate Surgery: A Systematic Review

Abstract: Background: Cleft lip and/or palate repair techniques require continued reevaluation of best practice through high-quality evidence. The objective of this systematic review was to highlight the existing evidence for patient safety and quality improvement (QI) initiatives in cleft lip and palate surgery. Methods: A systematic review of published literature evaluating patient safety and QI in patients with cleft lip and/or palate was conducted from database inception to June 9, 2022, using Preferred Reporting It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…Systematic review of quality improvement in cleft palate surgery has shown the most commonly supported intervention to be local bupivacaine use. 28 Epinephrine is also known to increase the length of action of bupivacaine providing a longer analgesic effect. 29 This was also found true in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Systematic review of quality improvement in cleft palate surgery has shown the most commonly supported intervention to be local bupivacaine use. 28 Epinephrine is also known to increase the length of action of bupivacaine providing a longer analgesic effect. 29 This was also found true in this study.…”
Section: Discussionmentioning
confidence: 99%